2022
DOI: 10.1038/s41523-022-00469-z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-basaloid variant of adenoid cystic carcinoma of the breast with near complete response to neoadjuvant chemotherapy

Abstract: Breast adenoid cystic carcinoma (AdCC) is a rare subtype of triple negative breast cancer. Two morphologic variants are described, namely classic AdCC (C-AdCC) and solid basaloid (SB-AdCC). Recent studies have shown that the SB-AdCC variant has significantly worse prognosis than C-AdCC. Due to the rarity of SB-AdCC, no standard recommendations are available for its management. Data on the use and benefit of chemotherapy in patients with SB-AdCC are sparse and the response to neoadjuvant chemotherapy has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Few databases are available to answer questions regarding the efficiency of NC. Grabenstetter et al [ 17 ] reported an excellent response to NC bases on doxorubicin plus cyclophosphamide each two weeks with G-CSF support for four cycles followed by carboplatin each 3 weeks for four cycles plus twelve cycles of weekly paclitaxel. This case can hypothesize the beneficial role of such therapy in providing a desirable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Few databases are available to answer questions regarding the efficiency of NC. Grabenstetter et al [ 17 ] reported an excellent response to NC bases on doxorubicin plus cyclophosphamide each two weeks with G-CSF support for four cycles followed by carboplatin each 3 weeks for four cycles plus twelve cycles of weekly paclitaxel. This case can hypothesize the beneficial role of such therapy in providing a desirable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of neoadjuvant/adjuvant CTH in ACC patients, even with axillary lymph involvement, remains unproven. Grabenstetter et al documented a positive response to neoadjuvant CTH in a patient with solid-basaloid variant ACC [15]. On other hand, the propensity score matched cohort by Yang et al inferred that adjuvant CTH did not significantly improve OS in ACC patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective series have shown no to marginal benefit from chemotherapy in these tumors 1 , 46 . The two less common subtypes, solid-basaloid and high-grade transformational adenoid cystic carcinoma, appear to have a more aggressive clinical course; and while numbers are small, benefit from chemotherapy in these subtypes cannot be ruled out 54 . Importantly, recent genomic analyses of solid-basaloid adenoid cystic carcinomas demonstrated that only a minority of these cancers harbor the cardinal molecular features of classic adenoid cystic carcinomas, suggesting that taxonomically, these solid-basaloid carcinomas likely constitute a convergent phenotype, with only a small subset being pathogenetically related to adenoid cystic carcinomas 53 .…”
Section: Introductionmentioning
confidence: 99%